Porous high-entropy alloy negative electrode material for lithium ion battery and preparation method of porous high-entropy alloy negative electrode material

By using porous and high -entropy alloys materials in lithium ion batteries, the use of acidic or alkaline etching to form a porous structure, solving the problem of structural damage caused by volume expansion in lithium ion batteries in lithium ion batteries, and achieve higher cycle stability. Sexual and battery life, while reducing costs.

CN119368747APending Publication Date: 2025-01-28HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411435100.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-28

Smart Images

  • Figure CN119368747A_ABST
    Figure CN119368747A_ABST
Patent Text Reader

Abstract

The invention relates to a porous high-entropy alloy negative electrode material for a lithium ion battery and a preparation method of the porous high-entropy alloy negative electrode material. Zn1 / 3Ge1 / 3Cu1 / 3Si1 / 3Mg1 / 3Al1 / 3P2 is etched through different acids and bases at normal temperature and normal pressure, and high-entropy alloy containing porous structures to different degrees is obtained. Due to the fact that the porous Zn1 / 3Ge1 / 3Cu1 / 3Si1 / 3Mg1 / 3Al1 / 3P2 high-entropy alloy has a large surface area capable of being in contact with an electrolyte and a proper space, the problems of particle smashing, electrode cracking, rapid attenuation of battery capacity and the like of a high-entropy alloy material can be solved, an electrochemical performance test is conducted on the porous Zn1 / 3Ge1 / 3Cu1 / 3Si1 / 3Mg1 / 3Al1 / 3P2 high-entropy alloy, and when the porous Zn1 / 3Ge1 / 3Cu1 / 3Si1 / 3Mg1 / 3Al1 / 3P2 high-entropy alloy serves as a lithium ion battery negative electrode material, the electrochemical performance of the porous Zn1 / 3Ge1 / 3Cu1 / 3Si1 / 3Mg1 / 3Al1 / 3P2 high- The battery has the advantages of good first coulombic efficiency, good reversibility, excellent electrochemical performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a porous high entropy alloy negative electrode material for lithium ion batteries and a preparation method thereof. Background Art

[0002] In recent years, high entropy materials have attracted widespread attention in the field of energy storage and conversion, especially in electrochemical energy storage materials. Based on the characteristics of high structural disorder, complexity of elemental composition and controllability of functions of high entropy materials, high entropy alloy-type negative electrode materials have obvious advantages in improving the reversible capacity, rate performance, cycle performance and reducing costs of negative electrode materials of lithium-ion batteries. However, during the charge and discharge cycle of high entropy alloys as negative electrodes of lithium-ion batteries, phosphorus-based high entropy alloys integrate many lithium storage active elements such as Zn, Ge, Si, Mg, Al, and P. These elements will successively alloy with Li during the lithiation process. For example:

[0003] Zn+xLi+xe - →Li x Zn (e.g. LiZn, volume expansion coefficient is about 100%)

[0004] Ge+xLi++xe - →Li x Ge (Example: Li 4.4 P, volume expansion coefficient is about 300%)

[0005] Si+xLi++xe - →Li x Si (e.g. Li 22 Si5, volume expansion coefficient is about 300%-400%)

[0006] Mg+xLi++xe - →Li x Mg(Example: Li 1.95 Mg, volume expansion coefficient is about 120%)

[0007] Al+xLi++xe - →Li x Al (e.g. β-LiAl, volume expansion coefficient is about 100%)

[0008] P+xLi++xe - →Li x P (e.g. Li3P, volume expansion coefficient is about 300%)

[0009] The above elements will produce large stress and strain during the lithiation process, resulting in severe volume expansion problems, which will eventually lead to particle crushing of high-entropy alloy materials, electrode cracking and rapid decay of battery capacity. Their poor cycle stability hinders the application of high-entropy alloys in the next generation of lithium-ion batteries. Summary of the invention

[0010] In view of this, the present invention proposes a porous high entropy alloy negative electrode material for lithium ion batteries and a preparation method thereof.

[0011] The technical solution of the present invention is achieved in this way:

[0012] A method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery, preferably, the preparation method comprises the following steps:

[0013] (1) Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials:

[0014] According to the molar ratio of zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus of 0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:1.5-2.5, zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus are mixed to obtain powder material, and the powder material is ball-milled to obtain Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 materials;

[0015] (2) Porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials:

[0016] The Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 material is etched, cleaned and dried to obtain porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al1 / 3 P2 materials;

[0017] The acidic etching solution includes one or more of 3-20wt% nitric acid solution, 3-20wt% boric acid solution, 3-20wt% hydrochloric acid solution, 3-20wt% hydrofluoric acid solution, and 10-30wt% hydrogen peroxide solution.

[0018] A method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery, preferably, the preparation method comprises the following steps:

[0019] (1) Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials:

[0020] According to the molar ratio of zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus of 0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:1.5-2.5, zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus are mixed to obtain powder material, and the powder material is ball-milled to obtain Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 material;

[0021] (2) Porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials:

[0022] Use alkaline etching solution to remove Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 material is etched, cleaned and dried to obtain porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 materials;

[0023] The alkaline etching solution includes 5-10 wt % sodium hydroxide solution and / or 5-10 wt % potassium hydroxide solution.

[0024] Preferably, in the ball milling, the mass ratio of steel balls to powder materials is 18-22:0.8-1.2; and the ball milling is carried out under an inert atmosphere.

[0025] Preferably, the ball milling speed is 300-500 rpm / min, and the ball milling time is 15-30 h.

[0026] Preferably, the ball milling further comprises intermittent ball milling, wherein the intermittent ball milling comprises: after ball milling for 0.5-1.5 hours, stopping ball milling for 20-40 minutes.

[0027] Preferably, the Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The mass volume ratio of the P2 material and the etching solution is 0.3-1g:10-40mL.

[0028] Preferably, the etching further comprises stirring at a rate of 400-600 rpm / min for 40-60 hours;

[0029] The drying temperature is 70-90° C. and the drying time is 6-10 hours.

[0030] Preferably, the etching further comprises performing multi-step etching using an acidic etching solution;

[0031] When performing multi-step etching, add acidic etching solution in each step and stir for 5 to 10 minutes before adding new acidic etching solution;

[0032] The acidic etching solution includes one or more of 5-10wt% nitric acid solution, 5-10wt% boric acid solution, 5-20wt% hydrochloric acid solution, 5-10wt% hydrofluoric acid solution, and 20-30wt% hydrogen peroxide solution;

[0033] Preferably, the preparation method obtains a porous high entropy alloy negative electrode material.

[0034] Preferably, the porous high entropy alloy negative electrode material is used in preparing the negative electrode of a lithium ion battery.

[0035] The present invention proposes to have similar atomic radii The synthesis of a new type of high-entropy alloy (HEA) is based on Zn, Ge, Si, Mg, Al, and P with similar electronegativity (P = 1.65-2.19), as well as Cu, a single element with high conductivity (5.7×107S / m), low price, and abundant resources. Among them, Zn, Ge, Si, Mg, Al, and P have lithium activity, while Cu maintains high conductivity output. This type of phosphorus-based high-entropy alloy has a large discharge capacity (1275mAh / g), a high first coulomb efficiency (86%), and a low and suitable discharge platform (0.5V), and is expected to become one of the ideal negative electrode materials for the next generation of high energy density lithium-ion batteries.

[0036] At the same time, Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 is subjected to liquid phase etching to modify its microstructure. HCl is used to etch away some elements (Zn, Mg, Al), while Ge reacts slowly and can be ignored. P can react with strongly oxidizing acids, and Cu and Si will not be etched without the participation of oxidants. The specific reaction mechanism is as follows:

[0037] Zn+2HCl→ZnCl2+H2↑

[0038] Mg+2HCl→MgCl2+H2↑

[0039] 2Al+6HCl→2AlCl3+3H2↑

[0040] Prepared porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P material, through its reserved porous structure space, buffers the volume expansion of the electrode material during the lithiation process, and is expected to maintain the integrity of the electrode structure morphology, thereby improving its cycle stability and battery cycle life.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] ① Compared with traditional expensive transition metal elements (Co, Mn, Ru, etc.), the present invention uses abundant and low-cost elements such as Zn, Cu, Si, Mg, Al, P, etc. to synthesize multi-element high-entropy alloys, which greatly reduces the material cost while maintaining the same level of electrochemical performance. The preparation method of the present invention is simple and feasible, and is easy to prepare, promote and use on a large scale.

[0043] ② Compared with Si single substance, the porous high entropy alloy prepared by the present invention has better cycle performance, and its porous structure is more conducive to alleviating the stress and strain of the structure during the lithiation process, buffering the volume expansion, and enabling the lithium battery to have better cycle stability.

[0044] ③ The method of high-energy ball milling combined with acid-base etching proposed in the present invention uses different acids and bases to etch high-entropy alloys to prepare a porous high-entropy alloy material. The porous structure can well alleviate the mechanical strain caused by the huge volume expansion during the cycle of the lithium battery, and the huge specific surface area increases the contact between the electrode and the electrolyte, greatly improving the battery cycle stability and service life. In addition, the etching method provided by the present invention can also be used to improve the cycle life and electrochemical properties of other alloy-type negative electrode materials, with a wide range of applications and simple feasibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Zn prepared in Examples 1-3 and Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 XRD patterns of P2 high entropy alloy and after different etchings.

[0046] Figure 2 The Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 SEM and element distribution diagrams of P2 high entropy alloy (a, b) and after etching with HNO3 (c, d), HCl (e, f), and NaOH (g, h), respectively.

[0047] Figure 3 The Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Energy dispersion diagram of P2 high entropy alloy (a) and after etching with HNO3 (b), HCl (c), and NaOH (d).

[0048] Figure 4 The Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al1 / 3 (a) Adsorption isotherm and (b) pore size distribution of P2 high entropy alloy after being etched by HNO3.

[0049] Figure 5 The Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The charge-discharge curves of P2 high-entropy alloy (a) and the first three cycles after being etched by HNO3 (b), NaOH (c), and HCl (d).

[0050] Figure 6 For Si single substance, Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Cycle life curves of P2 high entropy alloy and after being etched by HNO3.

[0051] Figure 7 The Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 XRD diagrams of the etching effects of P2 high entropy alloy and comparative example 2 of the present invention after being etched by different concentrations of HCl.

[0052] Figure 8 The Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 SEM images of the etching effects of P2 high entropy alloy and comparative example 2 of the present invention with different concentrations of HCl.

[0053] Fig. 9 The Zn prepared in Comparative Example 1 of the present invention 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 EDS graphs of the etching effects of P2 high entropy alloy and comparative example 2 of the present invention after being etched by HCl at different concentrations.

[0054] Fig.10 The XRD diagrams of the etching effects of comparative example 1 and embodiments 5-7 of the present invention after three-step etching are shown.

[0055] Fig.11 The SEM images of the etching effects of comparative example 1 and embodiments 5-7 of the present invention after three-step etching are shown.

[0056] Fig.12 It is the EDS graph of the etching effect of comparative example 1 and embodiments 5-7 of the present invention after three-step etching. DETAILED DESCRIPTION

[0057] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0058] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0059] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0060] The samples used in the examples and comparative examples of the present invention are as follows:

[0061] Table 1 Sample specifications, quality and manufacturer

[0062]

[0063]

[0064] Example 1

[0065] 1. For Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0066] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0067] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0068] 2. For porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0069] Nitric acid solution etching: First prepare a 5wt% HNO3 solution, weigh 0.5g Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / Add 3P2 high entropy alloy powder to a small beaker, and measure 20ml of 5wt% HNO3 solution and slowly pour it into the beaker containing the high entropy alloy powder to ensure that the powder is completely immersed in the solution. Then set the speed of 500r for magnetic stirring to ensure that the powder is evenly distributed to avoid local overreaction or unreaction. Continue stirring for 48h to ensure that the etching process is fully carried out. Use deionized water and anhydrous ethanol to wash alternately 3 times. The washed powder is placed in a vacuum drying oven at 80℃ and dried for 8h to remove moisture and organic solvents. During the drying process, ensure that the powder is evenly spread to speed up the drying speed and effect. After drying, take out the sample to obtain a porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder.

[0070] Example 2

[0071] 1. For Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0072] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0073] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0074] 2. For porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0075] Hydrochloric acid solution etching: First prepare a 5wt% HCl solution and weigh 0.5g Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / Add 3P2 high entropy alloy powder to a small beaker, and measure 20ml of 5wt% HCl solution and slowly pour it into the beaker containing the high entropy alloy powder to ensure that the powder is completely immersed in the solution. Then set the speed of 500r for magnetic stirring to ensure that the powder is evenly distributed to avoid local overreaction or unreaction. Continue stirring for 48h to ensure that the etching process is fully carried out, and use deionized water and anhydrous ethanol to wash alternately 3 times. The washed powder is placed in a vacuum drying oven at 80℃ and dried for 8h to remove moisture and organic solvents. During the drying process, ensure that the powder is evenly spread to speed up the drying speed and effect. After drying, take out the sample to obtain a porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder.

[0076] Example 3

[0077] 1. For Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0078] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0079] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0080] 2. For porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0081] Sodium hydroxide solution etching: First prepare a 5wt% NaOH solution and weigh 0.5g Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3Al 1 / 3P2 high entropy alloy powder is added to a small beaker, and 20 ml of 5wt% NaOH solution is measured and slowly poured into the beaker containing the high entropy alloy powder to ensure that the powder is completely immersed in the solution. Then set the speed of 500r for magnetic stirring to ensure that the powder is evenly distributed to avoid local overreaction or unreaction. Stirring is continued for 48 hours to ensure that the etching process is fully carried out. Deionized water and anhydrous ethanol are used to wash alternately 3 times. The washed powder is placed in a vacuum drying oven at 80°C and dried for 8 hours to remove moisture and organic solvents. During the drying process, the powder is ensured to be evenly spread to speed up the drying speed and effect. After drying, the sample is taken out to obtain a porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder.

[0082] Example 4

[0083] The method of Example 2 was used to prepare Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder was etched by HCl solutions of different concentrations, 5wt%, 10wt% and 20wt%.

[0084] 1. For Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0085] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0086] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0087] 2. For porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0088] Hydrochloric acid solution etching: First, prepare 5wt%, 10wt% and 20wt% HCl solutions, weigh 0.5g Zn 1 / 3 Ge 1 / 3Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder is added to a small beaker, and 20 ml of 5wt%, 10wt% and 20wt% HCl solutions are measured and slowly poured into the beaker containing the high entropy alloy powder to ensure that the powder is completely immersed in the solution. Then set the speed of 500r for magnetic stirring to ensure that the powder is evenly distributed to avoid local overreaction or unreaction. Stirring is continued for 48 hours to ensure that the etching process is fully carried out, and deionized water and anhydrous ethanol are used to wash alternately 3 times. The washed powder is placed in a vacuum drying oven at 80°C for 8 hours to remove moisture and organic solvents. During the drying process, the powder is ensured to be evenly spread to speed up the drying speed and effect. After drying, the sample is taken out to obtain a porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder.

[0089] Example 5

[0090] The etching is performed in a three-step etching method, wherein the first etching step and the second etching step use a 10 wt % H 2 O 2 solution, and the third etching step uses a 15 wt % HCl solution.

[0091] 1. For Zn 1 / 3 Ge 1 / 3 Cu1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0092] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0093] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0094] 2. For porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0095] First, prepare 10wt% H2O2 solution and 15wt% HCl, weigh 0.5g Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3P2 high entropy alloy powder is added to a small beaker, and 10ml of 10wt% H2O2 solution is slowly poured into the beaker containing the high entropy alloy powder, stirred for 5min, and then 10ml of 10wt% H2O2 solution is slowly poured into the beaker containing the high entropy alloy powder, stirred for 10min, and after waiting for 5min, 20ml of 15wt% HCl solution is added to ensure that the powder is completely immersed in the solution. Then set the speed of 500r for magnetic stirring to ensure that the powder is evenly distributed to avoid local overreaction or unreaction. Continue stirring for 48h to ensure that the etching process is fully carried out, and use deionized water and anhydrous ethanol to wash alternately 3 times. The washed powder is placed in a vacuum drying oven at 80℃ and dried for 8h to remove moisture and organic solvents. During the drying process, ensure that the powder is evenly spread to speed up the drying speed and effect. After drying, take out the sample to obtain a porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder.

[0096] Example 6

[0097] The etching is performed in a three-step etching method, wherein the first etching step and the second etching step use a 20 wt % H 2 O 2 solution, and the third etching step uses a 15 wt % HCl solution.

[0098] 1. For Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0099] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0100] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0101] 3. For porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0102] First, prepare 20wt% H2O2 solution and 15wt% HCl, weigh 0.5g Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3P2 high entropy alloy powder is added to a small beaker, and 10ml of 20wt% H2O2 solution is measured and slowly poured into the beaker containing the high entropy alloy powder, stirred for 5min, and then 10ml of 20wt% H2O2 solution is slowly poured into the beaker containing the high entropy alloy powder, stirred for 10min, and after waiting for 5min, 20ml of 15wt% HCl solution is added to ensure that the powder is completely immersed in the solution. Then set the speed of 500r for magnetic stirring to ensure that the powder is evenly distributed to avoid local overreaction or unreaction. Continue stirring for 48h to ensure that the etching process is fully carried out, and use deionized water and anhydrous ethanol to wash alternately 3 times. The washed powder is placed in a vacuum drying oven at 80℃ for 8h to remove moisture and organic solvents. During the drying process, ensure that the powder is evenly spread to speed up the drying speed and effect. After drying, take out the sample to obtain a porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder.

[0103] Example 7

[0104] The etching is performed in a three-step etching method, wherein the first etching step and the second etching step use a 30 wt % H 2 O 2 solution, and the third etching step uses a 15 wt % HCl solution.

[0105] 1. For Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0106] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0107] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0108] 4. For porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2

[0109] First, 10wt%, 20wt%, 30wt% H2O2 solution and 15wt% HCl were prepared, and 0.5g Zn 1 / 3 Ge 1 / 3Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3P2 high entropy alloy powder was added to a small beaker, and 10 ml of 30 wt% H2O2 solution was measured and slowly poured into the beaker containing the high entropy alloy powder, stirred for 5 minutes, and then 10 ml of 30 wt% H2O2 solution was slowly poured into the beaker containing the high entropy alloy powder, stirred for 10 minutes, and after waiting for 5 minutes, 20 ml of 15 wt% HCl solution was added to ensure that the powder was completely immersed in the solution. Then the speed was set to 500r for magnetic stirring to ensure that the powder was evenly distributed to avoid local over-reaction or non-reaction. Stirring was continued for 48 hours to ensure that the etching process was fully carried out, and deionized water and anhydrous ethanol were used to wash alternately 3 times. The washed powder was placed in a vacuum drying oven at 80°C for 8 hours to remove moisture and organic solvents. During the drying process, the powder was ensured to be evenly spread to speed up the drying speed and effect. After drying, the sample was taken out to obtain a porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder.

[0110] Comparative Example 1

[0111] The method of Example 1 was used to prepare Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder is no longer etched. The specific steps are as follows:

[0112] Zinc powder, germanium powder (Macklin, 99.999%), copper powder (Macklin, 99.9%), silicon powder (Aladdin, 99.9%), magnesium powder, aluminum powder and red phosphorus (Macklin, AR98.5%) are weighed and proportioned according to a specific molar ratio (0.33:0.33:0.33:0.33:0.33:0.33:2), and added into a stainless steel ball mill with a ball-to-material ratio of stainless steel beads to powder material of 20:1. The stainless steel jar is placed in a glove box filled with an inert atmosphere (Ar gas protection) (anhydrous and oxygen-free, with water and oxygen contents of <1ppm), and the stainless steel jar is sealed and covered in the glove box (locked and sealed with a locking device).

[0113] The stainless steel jar was taken out of the glove box, installed on the ball mill, fixed and tightened, and the speed of the ball mill was set to 400 rpm / min. The single ball milling time was 1 hour, the interval was 30 minutes, and the number of repetitions was 12 times, that is, the total ball milling time was 18 hours, and the high entropy Zn formed by Zn, Ge, Cu, Si, and P elements was obtained. 1 / 3 Ge1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 compound.

[0114] Test Case

[0115] The porous Zn prepared in Examples 1-3 above 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder, and Zn prepared in Comparative Example 1 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder was subjected to X-ray diffraction analysis, scanning electron microscope (SEM) analysis, EDS analysis, nitrogen isothermal adsorption-desorption test, pore size distribution analysis, electrochemical performance test, and long cycle performance test. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder, compared with Zn prepared in Comparative Example 1 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy powder was subjected to XRD, SEM and EDS tests.

[0116] Analyze the test results. Figures 1 to 12 .

[0117] Zn after different types of acid and alkali etching 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The X-ray diffraction pattern of P2 high entropy alloy is as follows Figure 1 As shown in the diffraction pattern, it can be seen that the high entropy alloy after etching is consistent with Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3Mg 1 / 3 Al 1 / 3The P2 diffraction peaks are consistent, indicating that it has not been oxidized after acid-base etching, no other impurities have been introduced, and it remains a single pure phase.

[0118] Ball milling synthesized Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy and Zn after being etched by HNO3, HCl and NaOH 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy was analyzed by scanning electron microscope (SEM). Figure 2 From the SEM image, it can be observed that the morphology of the high entropy alloy is composed of primary nanoparticles agglomerated into micron-sized secondary particles, with particle diameters ranging from one micron to several microns, and the primary particle size of its surface morphology is about 200-300nm. For different acid and alkali etching, the etching phenomenon of HNO3 is the most obvious. Compared with the high entropy alloy particles before etching, the surface after HNO3 etching is looser.

[0119] Figure 3 In the experiment, the elements were analyzed and it can be seen from the EDS image that Zn, Ge, Si, Cu, Mg, Al and P elements are evenly distributed.

[0120] Table 2 Changes in the element contents of Mg, Al, and P after etching with 5% HNO3, NaOH, and HCl

[0121]

[0122] In Table 2, it can be seen from the percentage of atoms that after different acid and alkali etching, the etching is mainly for Mg and Al elements. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The elemental proportions of Mg and Al in P2 decreased from 9.68% and 8.53% to 6.03% and 7.17% respectively; the elemental proportions of Mg and Al after HCl etching decreased to 4.37% and 6.14%; while the elemental proportions of Zn after NaOH etching decreased to 4.37% and 6.14% respectively. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3P2 is mainly the dissolution and etching of the P element, and its element proportion is reduced from 39.31% to 31.55%. Due to the large reduction in the content of the P element, the proportion of elements such as Mg and Al increases slightly.

[0123] As an important physical parameter of porous materials, specific surface area is not only closely related to its morphological characteristics, but also significantly affects its electrochemical properties. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 high entropy alloy and Zn etched by HNO3 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 high entropy alloy was subjected to nitrogen isothermal adsorption-desorption tests to further explore its specific surface area and pore structure characteristics. The test results are as follows: Figure 4 As shown. By comparative analysis, it can be seen that Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3Mg 1 / 3 Al 1 / 3 The specific surface area of ​​P2 high entropy alloy is 108.72m 2 / g, and its pore volume is 0.138cm 3 / g. In contrast, Zn etched by HNO3 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The specific surface area of ​​P2 high entropy alloy has increased to 112.76m 2 / g, and the pore volume also increased to 0.148 cm 3 / g, this difference indicates the effectiveness of HNO3 etching, and the porous morphology presented by SEM is consistent with the BET test results.

[0124] In order to gain a deeper understanding of the detailed information of the pore structure, the pore size distribution of the samples was further analyzed. Figure 4 As shown in b, Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 high entropy alloy mainly contains mesopores of 2 to 10 nm, and the Zn 1 / 3 Ge1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 In the pore size distribution diagram of P2 high entropy alloy, it can be observed that the number of pores in the range of 7 to 9 nm increases. This change in pore size is one of the main reasons for the increase in its specific surface area. It is worth noting that the rich pore structure space with high specific surface area can buffer the volume expansion of the electrode material during the lithiation process, maintain the integrity of the electrode structure morphology, and thus improve its cycle stability and battery cycle life.

[0125] from Figure 5 It can be seen that the synthesized Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 high entropy alloy electrode and the electrode etched by HNO3, NaOH, and HCl solutions provide 1335mAh / g, 1234mAh / g, 1225mAh / g, and 1202mAh / g capacity for lithium storage, respectively, while combining a low and suitable 0.5V lithiation platform. In addition, it is known that the synthesized Zn 1 / 3 Ge 1 / 3Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The reversibility of P2 high entropy alloy electrode and the series of high entropy alloys etched by HNO3, NaOH and HCl solutions for lithium-ion batteries is at a high level, with the first coulomb efficiency of 83% (Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3Mg 1 / 3 Al 1 / 3 P2), 86% (5% HNO3-HEA), 76% (5% NaOH-HEA), 80% (5% HCl-HEA). It can be seen that after etching, the porous high entropy alloy electrode material can still maintain the advantages of large capacity (>1200mAh / g), high first efficiency (86%), and low discharge platform (0.5V) of the electrode material.

[0126] Figure 6 In the case of a constant current charge and discharge at a current density of 100 mA / g, the battery capacity begins to decay after 30 cycles. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al1 / 3 The retention rate of P2 capacity is only 23%, while the Zn 1 / 3Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The capacity retention rate of the P2 electrode reaches 77%, indicating that the cycle life of the porous high-entropy alloy is effectively improved. In addition, it can be seen from the figure that the capacity of single silicon decays rapidly after 30 cycles, and the capacity retention rate is only 0.1%. In comparison, the cycle performance of the porous high-entropy alloy after etching has been improved by an order of magnitude. Its excellent cycle performance may be attributed to the porous structure that appears after being etched by HNO3, which is conducive to buffering volume expansion, thereby supporting the high reversibility and cyclability of lithium-ion batteries.

[0127] Figure 7 The high entropy alloys after etching with 5wt%, 10wt% and 20wt% HCl3 solutions were all 1 / 3 Ge 1 / 3Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 diffraction peaks are consistent, indicating that it has not been oxidized after acid-base etching, no other impurities have been introduced, and it remains a single pure phase.

[0128] Figure 8 In the experiment, the morphology of the high entropy alloy is composed of primary nanoparticles agglomerated into micron-sized secondary particles, with particle diameters ranging from one micron to several microns, and the primary particle size of its surface morphology is about 200-300nm. For the etching of 5wt% HCl, 10wt% HCl and 20wt% HCl hydrochloric acid, compared with the high entropy alloy particles before etching, the surface after etching is relatively loose, and the particle size is smaller after etching, and the agglomeration of small particles occurs. Among them, the surface of the high entropy alloy particles etched by 10wt% HCl and 20wt% HCl hydrochloric acid is looser than that of the high entropy alloy particles etched by 5wt% HCl hydrochloric acid.

[0129] Fig. 9 In the experiment, the elements were analyzed and it can be seen from the EDS image that Zn, Ge, Si, Cu, Mg, Al and P elements are evenly distributed.

[0130] Table 3 Changes in the element contents of Mg and Al after etching with 5%, 10%, and 20% HCl

[0131]

[0132] In Table 3, it can be seen from the percentage of atoms that after being etched by HCl at different concentrations, the etching is mainly for Mg and Al elements. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The elemental proportions of Mg and Al in P2 decreased from 9.68% and 8.53% to 4.73% and 6.14% respectively; the elemental proportions of Mg and Al after 10wt% HCl etching became 9.44% and 8.61%; while the elemental proportions of Zn after 20wt% HCl etching were 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The element proportions of Mg and Al in P2 dropped to 6.10% and 6.11% respectively.

[0133] Fig.10 The high entropy alloys after etching with 10wt%, 20wt%, 30wt% H2O2 solution and 15wt% HCl were all 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 diffraction peaks are consistent, indicating that it has not been oxidized after acid-base etching, no other impurities have been introduced, and it remains a single pure phase.

[0134] Fig.11 In the experiment, the morphology of the high entropy alloy is composed of primary nanoparticles agglomerated into micron-sized secondary particles, with particle diameters ranging from one micron to several microns, and the primary particle size of its surface morphology is about 200-300nm. For the etching of 10wt%, 20wt%, 30wt% H2O2 solution and 15wt% HCl, the etching phenomenon of 20wt% H2O2 solution and 15wt% HCl is the most obvious. Compared with the high entropy alloy particles before etching, the surface after etching is relatively loose. When it comes to 30wt% H2O2 solution and 15wt% HCl, due to the increase in etching concentration, the etched material has a smaller particle size, resulting in accumulation.

[0135] Fig.12 In the experiment, the elements were analyzed and it can be seen from the EDS image that Zn, Ge, Si, Cu, Mg, Al and P elements are evenly distributed.

[0136] Table 4 Changes in the element contents of Mg and Al after three-step etching with 10%, 20%, and 30% H2O2 mixed with HCl

[0137]

[0138]

[0139] In Table 4, it can be seen from the percentage of atomic proportion that after step-by-step etching with different concentrations of H2O2, the etching is mainly for Mg and Al elements. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The elemental proportions of Mg and Al in P2 decreased from 9.68% and 8.53% to 6.78% and 7.22% respectively; the elemental proportions of Mg and Al after 20wt% H2O2 etching decreased to 7.44% and 7.95%; and the elemental proportions of Zn after 30wt% H2O2 etching decreased to 7.44% and 7.95% respectively. 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The percentage of Mg and Al in P2 dropped to 7.60% and 6.75% respectively. For Mg and Al elements, the concentration of H2O2 did not significantly change the percentage of element content after etching. However, the etching effects of 10wt%, 20wt%, 30wt% H2O2 solution and 15wt% HCl on the elements Mg and Al were higher than those of 5wt% HNO3 and 5wt% NaOH, and there was no significant change with the etching effect of 5wt% HCl, indicating that three-step etching or multi-step etching can also achieve the desired effect, which can be determined according to the selected elements to be etched.

[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery, characterized in that: The preparation method comprises the following steps: (1) Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials: According to the molar ratio of zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus of 0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:1.5-2.5, zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus are mixed to obtain powder material, and the powder material is ball-milled to obtain Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 materials; (2) Porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials: The Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 material is etched, cleaned and dried to obtain porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 materials; The acidic etching solution includes one or more of 3-20wt% nitric acid solution, 3-20wt% boric acid solution, 3-20wt% hydrochloric acid solution, 3-20wt% hydrofluoric acid solution, and 10-30wt% hydrogen peroxide solution.

2. A method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery, characterized in that: The preparation method comprises the following steps: (1) Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials: According to the molar ratio of zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus of 0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:0.2-0.5:1.5-2.5, zinc powder, germanium powder, copper powder, silicon powder, magnesium powder, aluminum powder and red phosphorus are mixed to obtain powder material, and the powder material is ball-milled to obtain Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 material; (2) Porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 Preparation of P2 materials: Use alkaline etching solution to remove Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The P2 material is etched, cleaned and dried to obtain porous Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 P2 material; The alkaline etching solution includes 5-10 wt % sodium hydroxide solution and / or 5-10 wt % potassium hydroxide solution.

3. The method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery according to claim 1 or 2, characterized in that: In the ball milling, the mass ratio of the steel ball to the powder material is 18-22:0.8-1.2; the ball milling is carried out under an inert atmosphere.

4. The method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery according to claim 1 or 2, characterized in that: The rotation speed of the ball mill is 300-500 rpm / min, and the ball milling time is 15-30 hours.

5. The method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery according to claim 1, characterized in that: The ball milling also includes intermittent ball milling, wherein the intermittent ball milling is as follows: after ball milling for 0.5-1.5 hours, the ball milling is stopped for 20-40 minutes.

6. The method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery according to claim 1 or 2, characterized in that: The Zn 1 / 3 Ge 1 / 3 Cu 1 / 3 Si 1 / 3 Mg 1 / 3 Al 1 / 3 The mass volume ratio of the P2 material and the etching solution is 0.3-1g:10-40mL.

7. The method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery according to claim 1 or 2, characterized in that: The etching further comprises stirring at a rate of 400-600 rpm / min for 40-60 hours; The drying temperature is 70-90° C. and the drying time is 6-10 hours.

8. The method for preparing a porous high entropy alloy negative electrode material for a lithium ion battery according to claim 1, characterized in that: The etching further comprises performing multi-step etching using an acidic etching solution; When performing multi-step etching, add acidic etching solution in each step and stir for 5 to 10 minutes before adding new acidic etching solution; The acidic etching solution includes one or more of 5-10wt% nitric acid solution, 5-10wt% boric acid solution, 5-20wt% hydrochloric acid solution, 5-10wt% hydrofluoric acid solution, and 20-30wt% hydrogen peroxide solution.

9. The preparation method according to any one of claims 1 to 8 obtains a porous high entropy alloy negative electrode material.

10. Use of the porous high entropy alloy negative electrode material according to claim 9 in preparing a negative electrode of a lithium ion battery.